2001
DOI: 10.1016/s0008-6363(00)00196-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of eNOS in the therapeutic control of myocardial oxygen consumption by ACE inhibitors and amlodipine

Abstract: These results suggest that endogenous endothelial NO synthase derived NO serves an important role in the regulation of myocardial O(2) consumption. This action may contribute to the therapeutic action of ACE inhibitors and amlodipine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
5
6
0
Order By: Relevance
“…The findings of the present study support our previous work indicating that BK activates eNOS to regulate cardiac O 2 consumption and that this does not occur in the eNOS knockout mouse heart (16,18). More importantly, we demonstrated previously the transfer of NO from dog coronary microvessels coincubated with eNOS knockout mouse heart regulates tissue O 2 consumption (21).…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study support our previous work indicating that BK activates eNOS to regulate cardiac O 2 consumption and that this does not occur in the eNOS knockout mouse heart (16,18). More importantly, we demonstrated previously the transfer of NO from dog coronary microvessels coincubated with eNOS knockout mouse heart regulates tissue O 2 consumption (21).…”
Section: Discussionsupporting
confidence: 92%
“…NO has a number of beneficial effects in various systems and importantly functions as a physiological vasodilator in the coronary artery vascular bed, a regulator of mitochondrial respiration, a modulator of myocardial contractility, and a key metabolite in blood pressure regulation (1,30,32,59). Most of the functions for NO in the cardiovascular system are attributable to the enzyme eNOS, which is expressed in the endothelium as well as the cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (58) demonstrated that under hypoxic conditions, ATP and phosphocreatine are depleted significantly more in rat hearts with decreased concentration of functional Mb compared with hearts with normal levels of Mb. Several additional studies (1,32,59) have demonstrated that NO modulates oxygen mitochondrial respiration in the heart. NO has been shown to directly inhibit mitochondrial oxidative phosphorylation through reversible binding to cytochrome c oxidase (complex IV), where NO competes with dioxygen to bind at the binuclear Cu B /Fe a3 2ϩ site of cytochrome c oxidase (4-6, 11, 12, 46, 54, 56, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Loke et al 56 sought to determine whether amlodipine-derived NO regulated oxygen consumption in the heart from eNOSϪ/Ϫ mice. Amlodipine, like ramiprilat, had no effect on oxygen consumption in the eNOSϪ/Ϫ mouse heart.…”
Section: Stimulation Of No Synthesis By Amlodipinementioning
confidence: 99%